Ziarah Perspektif Kajian Budaya (Studi Pada Situs Makam Mbah Priuk Jakarta Utara ) - Syahdan, Syahdan (IAIN Palangka Raya, 2017)
Pilgrimage in this study tries to investigate from the perspective of cultural study, they are form (significant), function (application, interaction) and meaning (signifie). This study aimed to obtain information about the process of pilgrimage ritual at the tomb of Mbah Priuk, also trying to comprehend the function and meaning contained in the pilgrimage ritual activities conducted at the tomb of Mbah Priuk. The results obtained in this study show that all the informants who researcher encountered have similar view about Mbah Priuk. The people